The effects of Ficus carica on the activity of enzymes related to metabolic syndrome - Mopuri, Ramgopal; Ganjayi, Muniswamy; Meriga, Balaji; Koorbanally, Neil Anthony; Islam, Md. Shahidul (Journal of food and drug analysis, 2018)
The present study aimed to investigate the effects of the various parts of Ficus carica L. (figs) on antioxidant, antidiabetic, and antiobesogenic effects in vitro. Fruit, leaves, and stembark of the F. carica plant were sequentially extracted using organic and inorganic solvents and their total polyphenol and flavonoid contents were estimated. The effects of the extracts on antioxidative, antidiabetic (inhibition of α-amylase and α-glucosidase enzymes), and antiobesogenic (antilipase) activities were measured using several experimental models. The fruit ethanolic extract contained a high quantity of polyphenols and flavonoids (104.67±5.51 μg/mL and 81.67±4.00 μg/mL) compared with all other extracts. The activity of the ethanolic extract of F. carica fruit was significantly (p<0.05) higher than all other extracts and parts of the plant in terms of antioxidative, antidiabetic, and antiobesogenic effects. The IC50 values of the fruit ethanolic extract in terms of antioxidative (134.44±18.43 μg/mL), and inhibition of α-glucosidase (255.57±36.46 μg/mL), α-amylase (315.89±3.83 μg/mL), and pancreatic lipase (230.475±9.65 μg/mL) activity indicate that the activity of fruit ethanolic extract is better than all other extracts of the plant. The gas chromatography–mass spectroscopy analysis of the fruit ethanolic extract showed the presence of a number of bioactive compounds such as butyl butyrate, 5-hydroxymethyl furfural, 1-butoxy-1-isobutoxy butane, malic acid, tetradecanoic acid, phytol acetate, trans phytol, n-hexadecanoic acid, 9Z,12Z-octadecadienoic acid, stearic acid, sitosterol, 3,5-dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one, and 2,4,5-trimethyl-2,4-dihydro-3H-pyrazol-3-one. The results of this study suggest that the ethanolic extract of the fruit of F. carica may have potential antidiabetic and antiobesogenic agents. [Display omitted] •Fruit ethanolic extract of Ficus carica has potential inhibitory effects against carbohydrates and lipid digesting enzymes activities.•Above-mentioned extract may have potential antioxidative, antidiabetic and antiobesogenic agents.•Ficus carica fruit ethanolic extract may be potential alternative for the treatment of oxidative stress, type 2 diabetes and obesity. Further studies on humans and experimental animals are needed to confirm these effects.